Cost Management Knowledge Sebagai Pemoderasi Hubungan Antara Partisipasi Anggaran Dengan Kinerja Aparatur Pemerintah Sulawesi Tengah - Munayang, Olivia H. (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2018)
This study aims to determine whether budgetary participation affects the performance of the centralSulawesi government official and whether budgetary participation influences the performance of Central Sulawesi government official if moderated by cost management knowledge. Data collection techniques in this study were using questionnaires, observation and interviews. Respondents in this study were 66 Central Sulawesi Provincial Government officials. Data analysis used moderating regression analysis (MRA). The results showed that budgetary participation did not affect the performance of the Central Sulawesi government apparatus and budget participation did not affect the performance of the Central Sulawesi government apparatus if it was moderated by cost management knowledge.